GAMBARAN PERILAKU PENCEGAHAN PENULARAN COVID-19 PADA KELOMPOK USIA LANJUT DIWILAYAH KECAMATAN PAYUNG SEKAKI - Rahimulyani, Ranny; Zulfitri, Reni; Arneliwati, Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
The elderly are a high risk group for the occurrence of Covid-19 disease, so it is important to implement appropriate Covid-19 prevention behavior. This study aims to determine the description of the behavior of preventing the transmission of Covid-19 in the elderly group in the Payung Sekaki District area. This research is a quantitative study with a descriptive design. The sample in this study were 98 people using the Quota sampling technique. Data collection was carried out using a questionnaire of knowledge, attitudes and actions that had been declared valid and reliable, and the analysis used was univariate analysis. Most of the respondents have good knowledge 60.2%, good attitude 40.8%, and adequate action 57.9% in preventing Covid-19 transmission in the elderly group. Conclusion: The elderly in Payung Sekaki sub-district have positive behaviors in preventing the transmission of Covid-19.Keywords: Behavior,Covid-19, Elderly